Validation of a Simplified Implant-Retained Cantilever Fixed Prosthesis - Tribst, João Paulo Mendes [UNESP]; Rodrigues, Vinícius Anéas [UNESP]; Borges, Alexandre Luiz Souto [UNESP]; Lima, Dimas Rennó de [UNESP]; Nishioka, Renato Sussumu [UNESP] (Wolters Kluwer, 2018)
PURPOSE: To evaluate the stress and strain generated in a fixed four-element prosthesis under the application of axial and nonaxial loads using a simplified implant-supported fixed prosthesis model. MATERIALS AND METHODS: A 3-dimensional model was constructed containing 3 implants with a conventional anatomical prosthesis (G1). The second model with the same implant system received the simplified prosthesis (G2). A load of 300 N was applied at an axial point and a nonaxial point through finite element analysis software. RESULTS: The G2 group showed different values of stress concentration in the prosthesis, fixation screw, retention screw, and abutments when compared with G1. Within a limit of 10% degrees of acceptability, the stress on the implants and the bone strain were enclosed for both models of prostheses. CONCLUSION: The simplified fixed prosthesis evaluated presents biomechanical behavior similar to an anatomical prosthesis in the implants and in the surrounding bone structure.